Endocrine and Growth Disorders in Taiwanese Children With 22q11.2 Deletion Syndrome - Lin, Han-Yi; Tsai, Wen-Yu; Tung, Yi-Ching; Liu, Shih-Yao; Lee, Ni-Chung; Chien, Yin-Hsiu; Hwu, Wuh-Liang; Lee, Cheng-Ting (Frontiers in Endocrinology, 2022)
Background: Endocrine disorders are common in patients with 22q11.2 deletion syndrome (22q11.2DS). This study aimed to elucidate the clinical manifestations of endocrine disorders, including parathyroid, thyroid and growth disorders, in Taiwanese patients with 22q11.2DS. Methods: From 1994 to 2020, the medical records of 138 patients with 22q11.2DS diagnosed at a tertiary referral medical center in Taiwan were thoroughly reviewed retrospectively. Results: Hypocalcemia was detected in 57 of 135 patients (42%); 33 of 104 patients (32%) had hypoparathyroidism, and in 87% of them, hypocalcemia was detected before the age of one. Most patients had precipitating stressors during symptomatic hypocalcemic episodes. Eighteen of 29 patients had overt hypoparathyroidism at the last visit: 11 had persistent hypoparathyroidism and the other seven had recurrent hypoparathyroidism. Four of 84 patients had thyroid disorders, including thyroid developmental anomalies in two, dyshormonogenesis in one and Graves’ disease in one. Fifty of 126 patients (40%) had short stature. Age (odds ratio (OR) 0.91; 95% confidence interval (CI) 0.86-0.96; P<0.001) and airway anomalies (OR 2.75; 95% CI 1.04-7.31; P<0.05) were significant risk factors for short stature in multivariate logistic regression model. Twenty-eight of the 30 patients with airway anomalies were associated with severe congenital heart disease. Adult height standard deviation score (SDS) in 19 patients was significantly lower than target height SDS (-1.15±0.90 vs -0.08±0.65, P<0.001). Conclusions: Hypoparathyroidism is a common endocrine disorder in patients with 22q11.2DS. It is prudent to assess parathyroid function at diagnosis and during follow-up, especially in the presence of stress, to prevent symptomatic hypocalcemia. Although thyroid disorders are not so common as hypoparathyroidism, screening of thyroid dysfunction is justified in these patients. Patients with 22q11.2DS demonstrate a retarded growth pattern with a tendency of catch-up and regular monitoring of growth is indicated.